1992
DOI: 10.1088/0031-8949/45/6/008
|View full text |Cite
|
Sign up to set email alerts
|

Revised and extended analysis of five times ionized argon (Ar VI)

Abstract: R e v ise d and Exte nd e d A n a ly s is o f Five T im e s Ionized

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…In the present work, we used the LOPT (Kramida 2011) program to recalculate energy levels and study the uncertainties in wavelength measurements at VUV in this and our previous publications (Raineri et al 1992(Raineri et al , 2009. In this analysis, we consider all the lines shown in Table 1, excluding the transitions marked with the table footnote (j).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present work, we used the LOPT (Kramida 2011) program to recalculate energy levels and study the uncertainties in wavelength measurements at VUV in this and our previous publications (Raineri et al 1992(Raineri et al , 2009. In this analysis, we consider all the lines shown in Table 1, excluding the transitions marked with the table footnote (j).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous works, the line intensities for VUV were obtained under slightly different experimental conditions (Raineri et al 1992(Raineri et al , 2009. Here, we use line intensities from just one reference experiment, replacing previously published sets.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the configurations that were not observed experimentally we used energy parameters fixed at the ratios described above. We spent most of our efforts on the odd-parity configurations, basing this study on our previous research on the spectrum of Ar VI, 28 in which we found the levels of the 3s3p3d and the 3s3p4s configurations. The calculations 4, but for even-parity configurations.…”
Section: Structure Calculationsmentioning
confidence: 99%